Bóg jako życzliwy uczestnik procesu ewolucyjnego ? - Włodarska, Beata (Polskie Towarzystwo Religioznawcze, 2010)
Beata Włodarska – GOD AS A FRIENDLY PARTICIPANT OF THE EVOLUTIONARY PROCESS? In the past the picture of God did change in various ways. Almost every age is contributing something new in this matter. The achievements of science, discoveries, do influence not just the quality of life; the change occurs also in the human worldview. Man perceives the world in a different way, and he’s absorbed by other problems. Together with science, new discoveries and concepts he moves into an other space of imagination about the world. Galileo pointing his tele-scope into the sky, the thought of Newton or Darwin did change the mankind in a significant way. The Darwinian model seemed to deconstruct the traditional views. Along a common as-sumption, between the theory of evolution, in its common reception, and the teachings of the Church exists a ideological gap. Do we have to choose then between the option of religion or the option of science? The conflict attitude is not the only one; to avoid the argument we may ack-nowledge the independency of both disciplines – science and religion might belong to two diffe-rent orders. Such a preservative standpoint might be insufficient, because it doesn’t take into account a broader dimension of Christianity. Agency and knowledge about the world shouldn’t be separated, it is more about grasping their mutual relation. This article presents the thought of two French philosophers Ernest Renan and P. Teilhard de Chardin. Both thinkers come from the same country, both were raised in a Christian spirit, they are both of almost the same age, ho-wever each of them perceives differently the relation of science and religion. These two take almost opposite positions in this discussion.